Ethics in Scientific Research: A Literature Review of Fundamental Principles and the Identification of Research Misconduct - Agusta, Ratu Meri; Nurfalah, Siti; Komalasari, Rena; Nulhakim, Lukman (Papanda Publisher, 2025)
Ethics in scientific research is a crucial foundation for maintaining the quality, integrity, and trustworthiness of research outcomes. In an increasingly competitive academic environment driven by publication pressure, ethical violations such as fabrication, falsification, and plagiarism (research misconduct) have become serious threats to the credibility of the scientific community. This article aims to review recent literature on the fundamental principles of research ethics as well as methods for identifying and preventing scientific misconduct. By examining various academic sources, this review highlights the importance of ethics education based on contextual, interactive, and continuous training, along with the need for firm institutional policies to foster a responsible and dignified research culture. Furthermore, the article emphasizes the vital role of academic leadership and the involvement of all campus elements in the prevention and management of ethical violations in research.